Seroprevalence, Incidence and Risk Factors of Crimean-Congo Hemorrhagic Fever in Sistan-va-Baluchestan Province, Iran - K Holakouie Naieni; Sh Izadi; S Chinikar; A Nadim (Tehran University of Medical Sciences, 2004)
Since 1999, many cases of Crimean-Congo Hemorrhagic Fever have been reported from different parts of Iran. This study intended to define CCHF seroprevalence, incidence rates, and the most important risks in Sistan- Baluchestan province, Iran. Using cluster sampling with probability proportional to size, 310 subjects were selected from various districts of Zahedan and Zabol in the northern part of the province. Blood samples were drawn from consenting subjects, once at the beginning of the study and then 6 months later. The study began on 22 April 2003 and continued till 17 February 2004. A total of 18 out of 285 subjects who consented to give blood samples were actually positive by IgM and IgG capture ELISA tests. The calculated seroprevalence was 6.32% (95% CI: 3.24% to 9.40%). The calculated incidence was 0.48% (95% CI: 0.00% to 1.44%). Fourteen out of the 18 subjects with definitely positive IgG or IgM were female. In multivariate analysis, age, education, and history of slaughtering livestock were significantly related to the risk of infection. Only one of the seropositive subjects had a history of tick bite. This study shows the importance of subclinical infections in the epidemiology of this disease in Iran. It also seems that the risk of infection for housewives is high. Regardless of the high female to male ratio of seropositive subjects, it appears that the epidemiologic characteristics of the infection in this region are not so different compared to other parts of the world.